2013
DOI: 10.1002/app.39877
|View full text |Cite
|
Sign up to set email alerts
|

Fracture phenomena in micro‐ and nano‐layered polycarbonate/poly(vinylidene fluoride‐co‐hexafluoropropylene) films under electric field for high energy density capacitors

Abstract: The long-term dielectric lifetime properties of multilayered polycarbonate/poly(vinylidene fluoride-co-hexafluoropropylene) [PC/P(VDF-HFP)] films were measured as a function of the layer thickness. An optimum layer thickness of 160 nm was determined with the longest dielectric lifetime. The morphology of the damaged sites after dielectric breakdown was examined using scanning electron microscope. Acoustic emission detection system was coupled with the dielectric setup to correlate fracture events and dielectri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“…The forced assembly multilayer coextrusion process enables many polymeric systems having unique architectures to be produced including multilayer films, 10 cellular film/foam materials, 11–14 and fibrous membrane systems 9,15–18 . In addition, there has been numerous studies on the multilayered coextruded polymer systems directed toward applications including gas barrier films, 8,19 optical films, 20 shape memory films, 21–24 packaging film/foams, 25 fibrous membranes for filtration, 18,26 antibacterial membranes, 27,28 cellular membranes having through pores 12 and multilayer films with unique dielectric properties 29–36 . These investigations have emphasized the importance of scale within the multilayer films relative to enhanced performance characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The forced assembly multilayer coextrusion process enables many polymeric systems having unique architectures to be produced including multilayer films, 10 cellular film/foam materials, 11–14 and fibrous membrane systems 9,15–18 . In addition, there has been numerous studies on the multilayered coextruded polymer systems directed toward applications including gas barrier films, 8,19 optical films, 20 shape memory films, 21–24 packaging film/foams, 25 fibrous membranes for filtration, 18,26 antibacterial membranes, 27,28 cellular membranes having through pores 12 and multilayer films with unique dielectric properties 29–36 . These investigations have emphasized the importance of scale within the multilayer films relative to enhanced performance characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…However, a relatively increased breakthrough could be probably obtained according to references [18,19] which are attributed to the results from the barrier effect of the layers. Even such barrier effect can prolong the dielectric lifetime during breakdown progress [17,30].…”
Section: Sample Preparationmentioning
confidence: 99%
“…For miscible polymer blend systems, researchers found that the micro-layered structure could effectively enhance the dielectric performance, including dielectric constant, loss, strength and energy density. Dielectric performance of polymeric blends, such as PVDF/polycarbonate (PC) [15], linear low density polyethylene (LLDPE)/ethylene vinyl alcohol (EVOH) [16] and PC/Poly(vinylidene fluoride-cohexafluoropropylene) [17][18][19] were thoroughly studied by co-extruding multilayer structure, aiming to enhance the energy density for electronic and electrical power applications. Due to the well regular arrangement of the nano-inclusions and the amazing increase on the number of the layer, micro-layer co-extrusion obtained by layer multiplication technology becomes one of the popularly adopted methods in processing functional polymeric film or in molding containers [20].…”
Section: Introductionmentioning
confidence: 99%
“…The attractiveness of this technology has even led Dow to license it to the company EDI for commercial production and sale . It has been effectively demonstrated over the years that this technology has the capability to provide enhanced material properties in many polymer systems with wide ranges of application …”
Section: Introductionmentioning
confidence: 99%